CORRUPTION IN GOVERNMENT AS A GLOBAL PROBLEM - V. A. Sukhanov (Vestnik MGIMO-Universiteta)
The article focuses on the political consequences of corruption in government. The author analyzes the foreign and domestic experience in the fight against corruption. At the turn of the twentyfirst century the problem of corruption in the government of national states is attracting continuous international attention with the increasing role of interstate agencies and transnational actors in the struggle against it. The article discusses government corruption in the making as a global contemporary problem, proves the need for closer international cooperation to succeed in fighting against it. Political will of state’s leadership and successful functioning of the civil society institutions guarantee the adoption and consistent implementation of comprehensive anti-corruption programs. Special attention is paid to the method of determining the level of corruption in state. The author proposes a set of measures, which will improve the effectiveness of the fight against corruption.